Pemphigus and the terminal hair follicle. - Wilson, C; Dean, D; Wojnarowska, F (1991)
The scalp is frequently involved in the autoimmune skin disease pemphigus. This study demonstrates the distribution of pemphigus antigen in the scalp terminal hair follicle; as well as being found in the epidermis, it is distributed throughout the whole hair follicle outer root sheath and in the dermal bulb matrix cells. The increase in volume of target antigen offered by the follicular epithelium could be a factor determining scalp involvement in pemphigus.